Panel Data: Study Of Income Inequality In West Sumatra - Harahap, Erni Febrina; Yenti, Cintia Darma; Natasya, Natasya; Yusuf, Akmal (Universitas Gorontalo, 2025)
This research aims to analyze the factors that influence income inequality in West Sumatra Province. Some of the variables that are taken into consideration are: unemployment, education and poverty. The research uses secondary data from the Central Statistics Agency (BPS), using panel data regression analysis in 19 Regencies/Cities in West Sumatra Province, during 2017-2023. The selected research model uses the Fixed Effect Model (FEM). The research results show that: (1) the unemployment variable has a positive and insignificant effect on income inequality, (2) the education variable has a negative and significant effect on income inequality, (3) the poverty variable has a positive and significant effect on income inequality.